Application of Raman and Brillouin Scattering Phenomena in Distributed Optical Fiber Sensing - Muanenda, Yonas; Oton, Claudio J.; Di Pasquale, Fabrizio (Frontiers in Physics, 2019)
We present a review of the basic operating principles and measurement schemes of standalone and hybrid distributed optical fiber sensors based on Raman and Brillouin scattering phenomena. Such sensors have been attracting a great deal of attention due to the wide industrial applications they offer, ranging from energy to oil & gas, from transportation to structural health monitoring. In distributed sensors, the optical fiber itself acts as a sensing element providing unique measurement capabilities in terms of sensing distance, spatial resolution and number of sensing points. The most common configuration exploits optical time domain reflectometry in which optical pulses are sent along the sensing fiber and the backscattered light is detected and processed to extract physical parameters affecting its intensity, frequency, phase, polarization or spectral content. Raman and Brillouin scattering effects allow the distributed measurement of temperature and strain over tens of kilometers with meter-scale spatial resolution. The measurement is immune to electromagnetic interference, suitable for harsh environments and highly attractive whenever large industrial plants and infrastructures have to be continuously monitored to prevent critical events such as leakages in pipelines, fire in tunnels, structural problems in large infrastructures like bridges and rail tracks. We discuss the basic sensing mechanisms based on Raman and Brillouin scattering effects used in distributed measurements, followed by configurations commonly used in optical fiber sensors. Hybrid configurations which combine Raman and Brillouin-based sensing for simultaneous strain and temperature measurements over the same fiber using shared resources will also be addressed. We will also discuss advanced techniques based on pulse coding used to overcome the tradeoff between sensing distance and spatial resolution affecting both types of sensors, thereby allowing measurements over tens of kilometers with meter-scale spatial resolution.